Multi-Stakeholder Collaboration in Liquid Organic Fertilizer Production Training for Community Empowerment in Sukakarya Village: Pengabdian - Solina Balqis; Nurkayah; Rafikha Anggraini; Nadia Ulfa; Dayu Kristianto; Anggun Febiana; M. Agustian Alfarizi; Dwi Tusmila8; Malyan Khasanah Isnaini; Rohmadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aimed to enhance community capacity in managing household organic waste through training on liquid organic fertilizer (LOF) production in Sukakarya Village. The program was implemented using a multi-stakeholder collaboration involving university lecturers, an industrial partner (Pertamina), and the local women farmer group (KWT Melati). The activity adopted a participatory approach combining educational sessions, hands-on training, and evaluation through pre- and post-tests. Household organic waste such as vegetable residues, fruit peels, and leftover rice was processed using a simple anaerobic fermentation method with Effective Microorganisms 4 (EM4) as a bioactivator. The results showed a significant improvement in participants understanding of waste management, circular economy concepts, and LOF production procedures. In addition, participants demonstrated increased environmental awareness and readiness to independently produce LOF at the household level. Although the program was limited to the production stage without field application, the outcomes indicate strong potential for sustainable waste management and community empowerment. This initiative highlights the effectiveness of community-based education supported by multi-stakeholder collaboration as a replicable model for rural environmental sustainability programs.